A probabilistic load shedding concept considering highly volatile local generation. (May 2015) - Hauer, Ines; Wolter, Martin; Stötzer, Martin; Richter, Marc; Styczynski, Zbigniew A.
Highlights: Novel concept considers highly volatile generation from renewable energy sources. Static and dynamic verification of a probabilistic load shedding concept. The use of yearly average values leads to appropriate load shedding results. The proposed novel concept can replace the classical peak load concept. Abstract: Automatic load shedding is the ultimate countermeasure against imbalance in a power system and can effectively help preventing large blackouts. Taking into account a high penetration of renewable energy sources (RES) in the distribution grid, a clear distinction between load and generation at the PCC becomes increasingly more difficult. For that reason an adaptation of frequency relay parameters and their locations of installation are necessary. In Europe this is rest on a multi-step plan based on values such as the yearly peak load. In this paper a novel probabilistic method for automatic load shedding is presented that uses the average values instead of peak values for load shedding. Its applicability is verified by a dynamic power system model that was developed to compare the classical and novel probabilistic load shedding principle. The method is verified using data from a German TSO.